Intestinal antimicrobial peptides during homeostasis, infection, and disease - Muniz, Luciana R.; Knosp, Camille; Yeretssian, Garabet (Frontiers in Immunology, 2012)
Antimicrobial peptides (AMPs), including defensins and cathelicidins, constitute an arsenal of innate regulators of paramount importance in the gut. The intestinal epithelium is exposed to myriad of enteric pathogens and these endogenous peptides are essential to fend off microbes and protect against infections. It is becoming increasingly evident that AMPs shape the composition of the commensal microbiota and help maintain intestinal homeostasis. They contribute to innate immunity, hence playing important functions in health and disease. AMP expression is tightly controlled by the engagement of pattern recognition receptors (PRRs) and their impairment is linked to abnormal host responses to infection and inflammatory bowel diseases (IBD). In this review, we provide an overview of the mucosal immune barriers and the intricate crosstalk between the host and the microbiota during homeostasis. We focus on the AMPs and pay particular attention to how PRRs promote their secretion in the intestine. Furthermore, we discuss their production and main functions in three different scenarios, at steady state, throughout infection with enteric pathogens and IBD.